Flood-tolerant rice reduces yield variability and raises expected yield, differentially benefitting socially disadvantaged groups - Dar, Manzoor H.; de Janvry, Alain; Emerick, Kyle; Raitzer, David; Sadoulet, Elisabeth (Springer, 2013)
Approximately 30% of the cultivated rice area in India is prone to crop damage from prolonged flooding. We use a randomized field experiment in 128 villages of Orissa India to show that Swarna-Sub1, a recently released submergence-tolerant rice variety, has significant positive impacts on rice yield when fields are submerged for 7 to 14 days with no yield penalty without flooding. We estimate that Swarna-Sub1 offers an approximate 45% increase in yields over the current popular variety when fields are submerged for 10 days. We show additionally that low-lying areas prone to flooding tend to be more heavily occupied by people belonging to lower caste social groups. Thus, a policy relevant implication of our findings is that flood-tolerant rice can deliver both efficiency gains, through reduced yield variability and higher expected yield and equity gains in disproportionately benefiting the most marginal group of farmers.